Broadening horizons: molecular mechanisms and disease implications of endothelial-to-mesenchymal transition - Cheng Qian; Guanglu Dong; Chunmei Yang; Weiwei Zheng; Chongjin Zhong; Qiuhong Shen; Yin Lu; Yang Zhao (Cell Communication and Signaling)
Abstract Endothelial-mesenchymal transition (EndMT) is defined as an important process of cellular differentiation by which endothelial cells (ECs) are prone to lose their characteristics and transform into mesenchymal cells. During EndMT, reduced expression of endothelial adhesion molecules disrupts intercellular adhesion, triggering cytoskeletal reorganization and mesenchymal transition. Numerous studies have proved that EndMT is a multifaceted biological event driven primarily by cytokines such as TGF-β, TNF-α, and IL-1β, alongside signaling pathways like WNT, Smad, MEK-ERK, and Notch. Nevertheless, the exact roles of EndMT in complicated diseases have not been comprehensively reviewed. In this review, we summarize the predominant molecular regulatory mechanisms and signaling pathways that contribute to the development of EndMT, as well as highlight the contributions of a series of imperative non-coding RNAs in curbing the initiation of EndMT. Furthermore, we discuss the significant impact of EndMT on worsening vasculature-related diseases, including cancer, cardiovascular diseases, atherosclerosis, pulmonary vascular diseases, diabetes-associated fibrotic conditions, and cerebral cavernous malformation, providing the implications that targeting EndMT holds promise as a therapeutic strategy to mitigate disease progression.